Flow aggregated, traffic driven label mapping in label-switching networks. - Nagami, K. (IEEE Journal on selected areas in communications)
Label-switching technology enables high performance and flexible layer-3 packet forwarding based on the fixed-length label information that is mapped to the layer-3 packet stream. A label-switching router (LSR) forwards layer-3 packets based on their layer-3 address information or their label information that is mapped to the layer-3 address information. Two label-mapping policies have been proposed. One is traffic driven mapping, where the label is mapped for a layer-3 packet stream of each host-pair according to the actual packet arrival. The other is topology driven mapping, where the label is mapped in advance for a layer-3 packet stream toward the same destination network, regardless of actual packet arrival to the LSR. This paper evaluates the required number of labels under each of these two label-mapping policies using real backbone traffic traces. The evaluation shows that both label-mapping policies require a large number of labels. In order to reduce the required number of labels, we propose a label-mapping policy that is a combination of the two label-mapping policies above. This is traffic-driven label mapping for the packet stream toward the same destination network. The evaluation shows that the proposed label-mapping policy requires only about one-tenth as many labels as the traffic-driven label mapping for the host-pair packet stream and the topology-driven label mapping for the destination-network packet stream